2019
DOI: 10.3390/cancers11101423
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Heterogeneity in Epithelial Cell Fates of the Mammary Gland and Breast Cancer

Abstract: Fluidity in cell fate or heterogeneity in cell identity is an interesting cell biological phenomenon, which at the same time poses a significant obstacle for cancer therapy. The mammary gland seems a relatively straightforward organ with stromal cells and basal- and luminal- epithelial cell types. In reality, the epithelial cell fates are much more complex and heterogeneous, which is the topic of this review. Part of the complexity comes from the dynamic nature of this organ: the primitive epithelial tree unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…3D organoids are also suitable to studying the spatial interactions between cells of the same or different phenotype[ 62 ]. The cellular heterogeneity of the organoids can be explored using single-cell RNA sequencing[ 63 ]. Instead of primary cultures, some investigators try to create 3D organoids from cancer patient derived xenografts[ 52 , 60 , 64 ].…”
Section: Cancer Samplesmentioning
confidence: 99%
“…3D organoids are also suitable to studying the spatial interactions between cells of the same or different phenotype[ 62 ]. The cellular heterogeneity of the organoids can be explored using single-cell RNA sequencing[ 63 ]. Instead of primary cultures, some investigators try to create 3D organoids from cancer patient derived xenografts[ 52 , 60 , 64 ].…”
Section: Cancer Samplesmentioning
confidence: 99%
“…Capitalizing on FACS, we established that cocktails containing NGS Wnt/Rspo2 (“ RW ”) and EGF/NGS Wnt/Rspo2 (“ ERW ”) were roughly twice as efficient to sustain basal CD49f high /EpCAM medium cells compared to EGF alone (“ EGF ”) at day 5 ( Figure 5C ). This CD49f high /EpCAM medium population is described to contain stem cells (Samocha et al, 2019; Shackleton et al, 2006; Stingl et al, 2006). Further culture until day 13 in these three defined growth factor cocktails revealed three aspects; Firstly, only NGS Wnt/Rspo2 (“ RW ”) efficiently sustains basal cells (CD49f high /EpCAM medium ) over time.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor signals that that govern the coordination of the outgrowth of epithelium during puberty in the mammary gland are still being defined. The EGFR (Epidermal Growth Factor Receptor) family consists of EGFR (ErbB1/Her1), ErbB2/Her2, ErbB3/Her3, and ErbB4/Her4 with ligands that include EGF, transforming growth factor-alpha (TGFα), and amphiregulin (AREG) (Hynes & Watson, 2010; Samocha, Doh, Kessenbrock, & Roose, 2019). Elegant mixed tissue- and transplantation-approaches into cleared fat pad defined an essential role for EGFR signaling in stromal cells to promote ductal development (Sebastian et al, 1998; Sternlicht et al, 2005; Wiesen, Young, Werb, & Cunha, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Brenner et al reported the incidence of breast cancer in the Life Span Study of atomic bomb survivors and described that age at the menarche was a strong modifier of the radiation effect ( 49 ). The mammary gland is a highly dynamic organ that undergoes profound changes within its epithelium during puberty and the reproductive cycle ( 50 ). These changes are fueled by dedicated stem and progenitor cells ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mammary gland is a highly dynamic organ that undergoes profound changes within its epithelium during puberty and the reproductive cycle ( 50 ). These changes are fueled by dedicated stem and progenitor cells ( 50 ). Although the detailed mechanism by which irradiation during sensitive periods might stimulate breast cancer development remains unknown, there is more support for changes in tissue composition and stem cell regulation after irradiation.…”
Section: Discussionmentioning
confidence: 99%